2021
DOI: 10.2967/jnumed.120.260034
|View full text |Cite
|
Sign up to set email alerts
|

Cerenkov Luminescence Imaging in Prostate Cancer: Not the Only Light That Shines

Abstract: Introduction. Cerenkov luminescence imaging (CLI) is a novel imaging technology that might have the ability to assess surgical margins intra-operatively during prostatectomy using Gallium-68 prostate-specific membrane antigen ([ 68 Ga]Ga-PSMA-11). This study evaluates the accuracy of CLI compared to histopathology and as exploratory objective investigates the characteristics of the identified chemiluminescence signal.Materials and Methods. After intravenous injection of a mean 68 Ga-PSMA-11 activity of 69MBq i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Moreover, CLI holds the potential for managing infections as well. Previous studies have examined the use of fluorine‐18 ( 18 F) in the form of [ 18 F]FDG for CLI (Olde Heuvel et al, 2019, 2022). Based on our observations, CLI in animal models provided clear visualization of infection foci in the dorsal images at the site of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CLI holds the potential for managing infections as well. Previous studies have examined the use of fluorine‐18 ( 18 F) in the form of [ 18 F]FDG for CLI (Olde Heuvel et al, 2019, 2022). Based on our observations, CLI in animal models provided clear visualization of infection foci in the dorsal images at the site of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Heuvel reported that, with 68 Ga-prostate-specific membrane antigen ( 68 Ga-PSMA-11), CeLI could be used to assess surgical margins intraoperatively during prostatectomy. [73] In addition, beyond radioactive isotopes, therapeutic electron beams also produce Cerenkov luminescence and can be used for in vivo CeLI imaging. [74] Recently, Jia et al demonstrated that high-resolution optical luminescence sensing could be achieved during a standard dynamic treatment plan for a whole breast radiotherapy geometry.…”
Section: Cerenkov Luminescence Imaging (Celi)mentioning
confidence: 99%
“…Moreover, studies indicated that CeLI could be used to guide surgeries. Heuvel reported that, with 68 Ga‐prostate‐specific membrane antigen ( 68 Ga‐PSMA‐11), CeLI could be used to assess surgical margins intraoperatively during prostatectomy [73] . In addition, beyond radioactive isotopes, therapeutic electron beams also produce Cerenkov luminescence and can be used for in vivo CeLI imaging [74] .…”
Section: Molecular Light Applicationsmentioning
confidence: 99%
“…On the other hand, CLI is made possible by the fact that a significant fraction of the β + particles emitted by positron emitters have an energy (Table ) above the Cerenkov threshold in tissue (219 keV) and therefore are able to produce a detectable amount of Cerenkov radiation. This is why radiotracers labeled with fluorine-18 or carbon-11 like [ 18 F]­FDG, [ 18 F]­FET, [ 18 F]­FLT, [ 11 C]­choline, or peptides, proteins, antibodies, and nanovectors labeled with iodine-124 or radiometals (copper-64, , gallium-68, zirconium-89 ) have been used for bimodal PET/FLI. Even if several preclinical proofs of concept have been established today, CLI suffers of several weaknesses.…”
Section: Dual Pet/fluorescence Imaging Tools: Variety Of Examplesmentioning
confidence: 99%